Use Of Medical English Writing Corpus Among Contemporary Chinese Medical Students: A Needs-Based Analysis - Huanan Su (International Journal of Educational Management and Innovation, 2022)
The current research paper attempts to expose and analyze the general situation and the need for using meforcusersEnglish writing corpus among contemporary Chinese college medical students. At the same time, it makes efforts to uncover how to meet its needs. One hundred medical students participated in the research and were asked to answer questionnaires purposefully designed to collect comprehensive data regarding medical English writing corpus use. The current research results have shown a strong need to use medical English writing corpus among contemporary Chinese college medical students, as well as a severe lack of guidance from medical teachers in Chinese medical universities. Thus, this research further suggests that medical teachers should also guide medical students to meet the needs of selecting proper medical English writing corpus sensibly in their language learning process.